Francisco del Castillo S. J. (Lima, 1615-1673): autobiografía espiritual: formas, contenidos y significados (Pontificia Universidad Católica de Chile. Instituto de Historia, 2016)
Father Francisco del Castillo S. J. (Lima, 1615-1673), nominated to sainthood by the Society of Jesus in the Peruvian province, wrote his autobiography according the requirements of his superiors in order, as he states, to bring to light the mercy and blessings offered to him by God. In this work, he speaks above all of his inner life, thereby following the model of Saint Ignatius. Additionally, the autobiography accurately reflects the religious mentality of the era and the pastoral policies and strategies employed by the Society of Jesus in the Peruvian province during the 16th century. Father Francisco's biography is included in the Society's general policies as it is an historical account that identifies some common ideals, principles and paths.